Research on Causes of Corrosion Perforation in Changning Shale Gas Gathering Pipelines - QING Song-zhu, ZHANG Xiao-lin, WEN Zhan, DAN Xia, TANG Yu, KANG Lin, LIAO Ke-xi (Cailiao Baohu)
The transmission medium of shale gas gathering and transportation system is complex, which is easy to cause corrosion, perforation and leakage in the pipeline, seriously affecting the normal development and production of shale gas field.Based on the sampling analysis of perforated corrosion pipeline and transportation medium in Changning shale gas field, the results showed that the mole fraction of CO2 in the gas quality was 0.44%, and SRB(1.1×105/mL)and Cl-(21 913.14 mg/L)were detected in the water.Using SEM, EDS, XPS and other micro-analysis instruments to analyze the corrosion products in the gas collector, it was found that the corrosion products contained FeCO3(9.31%), FeS(3.54%), and FeS2(19.09%).Results showed that the main cause of the corrosion of the Changning shale gas production pipeline was the synergistic corrosion of CO2, SRB bacteria and Cl-.CO2 dissolved in the liquid film on the surface of the pipe wall, resulting in an acidic corrosion environment, and electrochemical corrosion of CO2 and Fe occurred.Pitting pits were formed and Fe2 +was produced.SRB bacteria transformed  in water quality into H2S, combining with Fe2+ to generate FeS and FeS2, and under the promotion of Cl-, quickly leading to corrosion perforation of pipelines.